Determinasi Intellectual Capital Disclosure Pada Perusahaan Keuangan Yang Listing Di Bursa Efek Indonesia - Saifudin, Saifudin (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2017)
Business competition in globalization era recently is very tight, so it is required intellectual capital disclosure because it can give enough information to create value of company. The purpose of this research is to examine the relationship between intellectual capital disclosure as dependent variable and company size, leverage, profitability, company age, independent commissioner, and ownership consentration as independent variables. The research was conducted using secondary data from company financial report and annual report are listed in the IDX in 2014. The research samples were 76 companies consists of banking, financial institutions, securities, and insurance companies which have been selected using purposive sampling method. The analysis method used was multiple linear regression. The result show that leverage and profitability have influence on intellectual capital disclosure. Meanwhile, company age, independent commissioner, and ownership concentration have no influence on intellectual capital disclosure.